Measurements of the structure and circulation of the stratosphere and mesosphere, 1970 - Smith, Walter S.; United States. National Aeronautics and Space Administration.; Goddard Space Flight Center. (Washington, D.C. : National Aeronautics and Space Administration, 1972)
MESOSPHERE; METEOROLOGICAL CHARTS; SOUNDING ROCKETS; STRATOSPHERE; ATMOSPHERIC CIRCULATION; ATMOSPHERIC COMPOSITION; ATMOSPHERIC DENSITY; ATMOSPHERIC PRESSURE; ATMOSPHERIC TEMPERATURE; TABLES (DATA); METEOROLOGICAL OBSERVATIONS; PRESSURE; DENSITY; WIND; ACOUSTIC GRENADE EXPERIMENTS "Complete data from a total of 26 meteorological rocket soundings of the stratosphere and mesosphere conducted from Barrow, Alaska; Churchill, Canada; and Wallops Island, Va., are presented. These data consist of temperature, pressure, density, and wind profiles from 16 acoustic grenade soundings that cover the 30- to 90-km altitude range, and temperature, pressure, and density profiles from 10 pitot probe soundings that cover the 25- to 120-km altitude range. Errors for each of the 16 grenade soundings are also included. No analysis of the meteorological significance of the data is attempted."--NTIS abstract. Prepared at Goddard Space Flight Center. Cover title. Includes bibliographical references (p. 4). MESOSPHERE; METEOROLOGICAL CHARTS; SOUNDING ROCKETS; STRATOSPHERE; ATMOSPHERIC CIRCULATION; ATMOSPHERIC COMPOSITION; ATMOSPHERIC DENSITY; ATMOSPHERIC PRESSURE; ATMOSPHERIC TEMPERATURE; TABLES (DATA); METEOROLOGICAL OBSERVATIONS; PRESSURE; DENSITY; WIND; ACOUSTIC GRENADE EXPERIMENTS "Complete data from a total of 26 meteorological rocket soundings of the stratosphere and mesosphere conducted from Barrow, Alaska; Churchill, Canada; and Wallops Island, Va., are presented. These data consist of temperature, pressure, density, and wind profiles from 16 acoustic grenade soundings that cover the 30- to 90-km altitude range, and temperature, pressure, and density profiles from 10 pitot probe soundings that cover the 25- to 120-km altitude range. Errors for each of the 16 grenade soundings are also included. No analysis of the meteorological significance of the data is attempted."--NTIS abstract. Mode of access: Internet.